2021
DOI: 10.3390/ijms22158339
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Structure of Protein Sequence

Abstract: Most non-communicable diseases are associated with dysfunction of proteins or protein complexes. The relationship between sequence and structure has been analyzed for a long time, and the analysis of the sequences organization in domains and motifs remains an actual research area. Here, we propose a mathematical method for revealing the hierarchical organization of protein sequences. The method is based on the pentapeptide as a unit of protein sequences. Employing the frequency of occurrence of pentapeptides i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…Tales características estructurales resultan de propiedades comunes a todas las cadenas peptídicas (Ealy, 2022), que se forman mediante los enlaces de hidrógeno que estabilizan el esqueleto polipeptídico (Sanvitore & Farci, 2022). Nekrasov et al (2021), analizaron la estructura de las proteínas globulares utilizando diagramas de empaquetamiento, demostrando cómo la disposición de segmentos de estructura secundaria a lo largo de la secuencia se relaciona con propiedades tridimensionales, como las hojas paralelas y antiparalelas.…”
Section: Estructura De Las Proteínasunclassified
“…Tales características estructurales resultan de propiedades comunes a todas las cadenas peptídicas (Ealy, 2022), que se forman mediante los enlaces de hidrógeno que estabilizan el esqueleto polipeptídico (Sanvitore & Farci, 2022). Nekrasov et al (2021), analizaron la estructura de las proteínas globulares utilizando diagramas de empaquetamiento, demostrando cómo la disposición de segmentos de estructura secundaria a lo largo de la secuencia se relaciona con propiedades tridimensionales, como las hojas paralelas y antiparalelas.…”
Section: Estructura De Las Proteínasunclassified
“…A total of 11 levels of protein organization with elements ranging from 7 to 56 amino acid residues were found in the protein sequence set. The organization levels were assumed to correspond to super-secondary structure elements of different topologies (Mikhalskii et al 2020;Nekrasov et al 2020Nekrasov et al , 2021.This method uses the pentapeptide as a unit of protein sequence and has been successfully used in the development of recombinant proteins, the study of the principles of enzyme functioning, and the finding of the minimum functional site in proteins. We analyzed 44,860 structures of peptides by the molecular dynamics method and found that 1,225 pentapeptides over 80% of the simulation time were in a stable conformation.…”
Section: Contributions To Biophysicsmentioning
confidence: 99%
“…Overall, the "Medical Genetics, Genomics and Bioinformatics" series collected 28 articles and reviews. This 2021 Special Issue is focused on the analysis of cancer progression [12], genetics mechanisms of cancers [13,14], and bioinformatics theory development [15].…”
mentioning
confidence: 99%
“…Alexei Nekrasov et al [15] presented theoretical work on the analysis of hierarchical organization of protein sequences. The authors developed a modeling method based on the pentapeptide as a unit of protein sequences.…”
mentioning
confidence: 99%